Reliability analysis of offshore structures under wave load - Li, Hongliang. (2009)
This progress report deals with the procedures and findings of final year project ST-47AB: Reliability Analysis of Offshore Structures under Wave Load. This would include background information on the project, literature review of concepts and information related to using the dynamic analysis capabilities of GT STRUDL/GT SELOS software to perform a reliability analysis. A methodology for the steps takin in this project to attain the required results will be provided. Findings from analysis of the various results will also be discussed in the concluding chapter of the report.